An introduction to object-oriented programming with UML using borland C++ - Rosziati Ibrahim (Penerbit Universiti Tun Hussein Onn Malaysia, 2008)
This book introduces object-oriented programming using Borland C++ programming language through an approach that uses examples programs. This approach simplifies and reinforces the learning process.